PENGARUH JUMLAH INDIVIDU DALAM KANDANG PENANGKARAN TERHADAP KONSUMSI PAKAN DAN NUTRISI PADA BURUNG PERKICI PELANGI (Trichoglossus haematodus) - Tri - Haryoko (Masyarakat Zoologi Indonesia, 2008)
Haryoko, T. 2008. Effect of density in cage upon feed intake and nutrition level inTrichoglossus haematodus. Zoo Indonesia 17(1):21-26. Trichoglossus haematodusis Psittacidae family which have diet on nectar. Inballance on nutrition contents orincomplete diet is a common problem in birds captivity. The aim of this researchwas to study the effect of bird density in cage upon feed intake and nutrition level.The research was conducted from April to July 2006. Bird density in each cage was2, 3 and 9 birds. The composition of diet consisted of 4.7% protein,1.3% fat, 1.5%crude fiber, 0.19% calsium, 0.17% fosfor and 1,256 kkal metabolism energy. Feedintake for Group A was 87.65 g/bird/day, group B was 80.37 g/bird/day and Group Cwas 81.92 g/bird/day, respectively. The result showed a correlation between bird’sdensity and feed intake as the density increased birds got less amount of food andnutrition.